Implementasi Bahasa Phyton Untuk Clusterisasi Data Penjualan Menggunakan Metode K-Means - Hellyana, Corie Mei (Informatics and Computer Engineering Journal, 2023)
In a business or trade, the process of keeping stock of goods is one way to provide customer satisfaction. To fulfill this, business owners must be able to analyze which goods or products are selling well, selling well and not selling well in the market, not an easy thing if the business has hundreds or even thousands of products sold every month. This problem can be solved by clustering sales products using the K-Means method. In the clustering process using the Python programming language which is object oriented which produces 3 clusters, where 1 cluster is for products that sell well, the next 2 clusters for products that are selling well and not selling well. The results of this clusterization can later be used by business owners in maintaining inventory and establishing sales strategies.